Educational Participation and the Psychological Challenges of Adolescents in the Digital Era: A Qualitative Analysis of the East Java Education System - Mayang Putri Imansari; Gaddy Indra; Muhammad Batderu Syamsi; Rena Sari; Syarif Sultan Bhanurasmi (P3I UMSurabaya, 2025)
This study examines the dynamics of adolescent educational participation in East Java amid digital transformation using a qualitative, library-based approach. Drawing on data from the Central Statistics Agency (BPS) and academic literature, the research identifies a slight yet significant decline in school participation, especially among adolescents aged 16–18. The decline is linked to economic constraints, unequal school distribution, and fluctuating learning motivation. The findings highlight that educational success should be assessed not only by enrollment numbers but also through social, psychological, and technological factors. The study advocates for a holistic educational framework that promotes equal access, digital literacy, and character development to create a more adaptive and sustainable education system.